Effect of silica coating on the bond strength of milled pure titanium to dental porcelain. (8th July 2016) - Ye, Jiantao; Ye, Xiuhua; Chang, Shaohai; Liu, Lang; Zhang, Yiping; Lin, Shiyao
Abstract : The creation of a high bond strength between machined computer‐manufactured pure titanium and porcelain remains problematic, and the effects of a silica coating on the bond strength of milled pure titanium bonded to dental porcelain require further investigation. The objective of this study was to evaluate the bond strength of machined pure titanium, with an intermediate coating of silica, to dental porcelain. In this work, 24 specimens of milled pure titanium were prepared and randomly divided into test and control groups, in which the test group was coated with silica using the sol‐gel dipping technique. The metal–ceramic bond strength was evaluated, according to ISO 9693 standards, using the three‐point bending test, and scanning electron microscopy and energy‐dispersive spectroscopy were used to study the microstructure and elemental composition of the specimens. The bonding strength of the silica‐coated group was significantly higher than that of the control group, and more residual porcelain on the metal surface could be observed in the silica‐coated group. Therefore, the application of a silica intermediate coating produced using the sol‐gel method could significantly improve the bond strength between machined pure titanium and porcelain.